Why I Believe Becoming Peircean is Preferable - Merrell, Floyd (Signs - International Journal of Semiotics, 2007)
North American philosopher and polymath, Charles S. Peirce, was frequently drawn toward apparently unanswerable questions. This led him to answers that were ahead of his times, as witnessed by work on Peirce among quantum physicists, biologists, ecologists, social scientists, historians, and philosophers. Nevertheless, most, if not all, ‘neopragmatists’ often wish to ignore him. This is unfortunate. For, Peirce’s concept of the sign, tantamount to his view of logic, especially in regard to the implications of two key terms, vagueness and generality, reveal a practicing philosophy, that, of processual nature, resists that age‐old mire of dualistic thinking.